ZIARAH KUBUR, NILAI DIDAKTIS DAN REKONSTRUKSI TEORI PENDIDIKAN HUMANISTIK - Abd. Aziz (IAIN Tulungagung, 2018)
As a form of da’wah, the grave pilgrimage has didactic function. Some didactic values contained in the pilgrimage of the grave are the exemplary to the charismatic figures, the transformation of remembering death as a spirit of the good deed, the building of social capital, the medium of gratitude, and of order and obedience. One of the challenges faced in Indonesian education is the rampant violence done by students and parents to teachers. This problem can not be solved only through the application of the concept of humanistic education. Therefore, the author offers the concept of humanistic religious education. This concept contains the use of some didactic values of the grave pilgrimage to complement the weaknesses of the concept of humanistic education. The use of didactic value is motivated by the reason that the grave pilgrimage is the religious practice that is easily accessible to the public from all social classes, except for those who reject it. Some of the companion values of the concept of humanistic education are the sacralization of the function of the teacher, the transformation of remembering death for charity and commitment to order and obedience. The sacralization of teachers is necessary to awaken parents and students that violence to teachers can lead to quality for perpetrators of violence. The concept of charity should be maintained in education to encourage the awareness of parents and students to not only need to respect the teacher during the learning process, but also to continue after the student completes his education. Commitment to obeying the order is necessary so that the parents and the student do not resort to violence to the teacher when the teacher carries out his disciplinary duties.